An elevated systolic blood pressure response at 8 minutes in full contact exercise may identify hypertensive subjects - Baker, J.; Davies, B.; McCormick, M. C.; Graham, M. (Research in Sports Medicine, 2013)
The aim of this study was to identify hypertension (HT) in karate competitors (KCs) in high intensity exercise. Values were compared with an exercise control group (EC). The 84 subjects were randomly divided into two groups: KC and EC. Resting blood pressure (BP) was measured the day before and immediately precompetition. A further three measurements were taken postexercise for all subjects at 1-, 2-, and 8- minute intervals. At rest, day one, mean BP of KC was 134/84 ± 3/2 mmHg vs. EC, 124/72 ± 1/2 mmHg and on day 2, was 141/79 ± 3/2 mmHg vs. EC, 125/72 ± 1/2 mmHg, respectively. Eight minutes postcompetition, BP of KCs was 140/77 ± 2/1 mmHg vs. EC 135/75 ± 2/1 mmHg. High blood pressure (HBP) was recorded in 60.5% of KCs on day 2, and essential HT that required medical therapy was subsequently diagnosed in 5% of KCs. Five percent of EC also had HBP, but subsequent medical examination reported normal values.